Study on the Ignition Process and Characteristics of the Nitrate Ester Plasticized Polyether Propellant - Xiaoting Yan; Zhixun Xia; Liya Huang; Likun Ma; Xudong Na; Yunchao Feng; Chuanbo Fang (International Journal of Aerospace Engineering)
In this study, a CO2 laser ignition experimental system was built to study the ignition process and characteristics of the Nitrate Ester Plasticized Polyether (NEPE) propellant. The effect of the energy density, ingredients, and the grain size distribution of the propellant on the ignition process was investigated using a CO2 laser igniter, a high-speed camera, and a tungsten-rhenium thermocouple. Four types of NEPE propellants were tested under different laser heat fluxes, and the ignition delay time, the ignition temperature, and the ignition energy were obtained. Experimental results show that the ignition process of the NEPE propellant can be divided into three stages, namely the first-gasification stage, the first-flame stage, and the ignition delay stage. When the energy density is lower than the ignition energy threshold, the ignition process cannot be achieved even under continuous energy loading. The increase of the energy density can lead to the decrease of the ignition delay time but has little effect on the ignition temperature. The ingredients and grain size distribution have great effects on both the ignition delay time and the ignition temperature. The grain size effect of aluminum is the largest compared with that of Ammonium Perchlorate (AP) and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX), while the grain size effect of AP is larger than that of HMX.